KAJIAN YURIDIS TERHADAP PENERAPAN SANKSI PIDANA DALAM PERKARA KORUPSI Nomor 29/Pid.Sus-TPK/2021/PN.JKT.PST - Rendradi Suprihandoko (Kajian Hukum, 2022)
By looking at the current conditions and practice of law enforcement of corruption in Indonesia, the formulation of the problem can be formulated as follows: 1] How are Criminal Sanctions Arranged according to Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption (UUPTPK). in Indonesia ? 2]. How is the application of criminal sanctions in Case Number 29/Pid.Sus TPK/2021/PN.JKT.PST? 3]. What are the solutions or solutions so that the implementation of the criminal sanctions system can be more effective? The research method used is normative juridical, namely by looking at the products of applicable legislation and juxtaposing it with law enforcement practices that already have permanent legal force. Thus, it will be easier for the author to answer the formulation of the problem in this paper. From the author's observation, there are not many corruption cases that can be charged with the death penalty. Even if there is such a case and it fulfills the formulation of the offense according to the public's view, the Prosecutor will not necessarily demand and the Judge impose a death penalty against the defendant. As an example of the corruption case of the Social Assistance Fund at the Ministry of Social Affairs in Jakarta with the defendant JPB, according to the author, it complies with Article 2 paragraph 1 and paragraph 2 of the UUPTPK. But the facts say otherwise, the defendants were only prosecuted, tried and sentenced to imprisonment and other additional penalties according to Article 12 letters b and 18 of the PTPK Law. The 3 {three} Articles should be applied as the legal basis.